Pelvic floor muscle assessment on three‐ and four‐dimensional transperineal ultrasound in women with ovarian endometriosis with or without retroperitoneal infiltration: a step towards complete functional assessment. (25th June 2018) - Mabrouk, M.; Raimondo, D.; Del Forno, S.; Baruffini, F.; Arena, A.; Benfenati, A.; Youssef, A.; Martelli, V.; Seracchioli, R.
ABSTRACT: Objectives: Previous studies comparing women with deep infiltrating endometriosis (DIE) and healthy controls have underlined an association between pelvic floor muscle (PFM) hypertonic dysfunction and deep lesions. The aim of this study was to compare the morphometry of PFM in women affected by ovarian endometriosis with DIE vs those without DIE in order to assess the impact of retroperitoneal infiltration by the disease on PFM function. Methods: This was a prospective study conducted between March 2015 and December 2016 on symptomatic women with a clinical and sonographic diagnosis of ovarian endometriosis with or without DIE, scheduled for laparoscopic surgery. We excluded patients with current or previous pregnancy, previous surgery for deep endometriosis, other causes of chronic pelvic pain or congenital or acquired abnormalities of pelvic floor anatomy. Three‐ and four‐dimensional transperineal ultrasound was performed to evaluate PFM morphometry and assess levator hiatal area (LHA) and diameters at rest, during PFM contraction and during Valsalva maneuver. All volumes were analyzed offline by an investigator blinded to the clinical data. Results: One hundred and fourteen patients with ovarian endometriosis were enrolled in the study, 75 with DIE and 39 without DIE. The diagnosis of endometriosis was confirmed by histological examination in all patients. Compared with women without DIE, women with DIE showed a smaller LHA at rest, during contraction and during Valsalva maneuver ( P = 0.03, P = 0.03 and P = 0.02, respectively) and a smaller reduction in LHA during PFM contraction ( P = 0.04). Conclusions: Women with ovarian endometriosis who were affected by DIE showed smaller hiatal dimensions than did women without DIE. Considering that PFM dysfunction in patients with DIE could cause pain symptoms and pelvic organ dysfunction, transperineal ultrasound could allow a more complete functional assessment and tailored therapy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.